The Supply and Demand for Exports: A Simultaneous Approach - Goldstein, Morris; Khan, Mohsin S. (The Review of Economics and Statistics, 1978)
The following sections are included:INTRODUCTIONTHEORETICAL SPECIFICATION OF THE EXPORT FUNCTIONSRESULTSCONCLUSIONAPPENDIXREFERENCES